Optimization of Bioethanol Production Using an Enzymatic Hydrolysis Process with Green Algae (Chaetomorpha) as the Raw Material - Maimun, Teuku; Lubis, Mirna Rahmah; Zein, Muhammad Aldi; Ali, Wahed Febbry Andriansyah (Makara Journal of Technology, 2024)
Bioethanol is an alternative fuel derived from biological feedstock used to decrease the reliance on fossil fuels because of increasing energy consumption associated with population growth and increased use of oil fuels. Bioethanol production has been widely conducted using several types of algae, but the optimal conditions for the hydrolysis and fermentation processes are not explained in more detail. Therefore, this study focuses on determining the optimal conditions for hydrolysis and fermentation to maximize the bioethanol yield. This study uses optimization based on the hydrolysis time, temperature, and pH to increase the reducing sugar content using high-performance liquid chromatography in the enzymatic hydrolysis process. The process consists of liquefaction and saccharification steps, where 4% α-amylase enzyme and 2%, 3%, and 4% glucoamylase are used. Results showed that the optimal conditions for the hydrolysis time were 180 min at temperatures of 70 °C to 80 °C. The enzymatic hydrolysis process is conducted under optimal conditions, followed by the fermentation process. Finally, the distillation process was performed with a maximum bioethanol yield of 25.0%.